2019
DOI: 10.1042/bsr20181465
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 acts as a sponge of miR-204 to up-regulate CXCR4 expression and promote prostate cancer progression

Abstract: Prostate cancer (PCa) is a devastating malignant disease with a poor prognosis. The aim of current study is to investigate the role of lncRNA-urothelial carcinoma associated 1 (UCA1) in the progression of PCa. We evaluated the expression levels of UCA1 in a total of 16 benign prostatic hyperplasia tissues (BPH) and 40 PCa tissues, as well as PCa cells. The functional regulatory effects of UCA1 were investigated using a series of cell function approaches. Our data showed that UCA1 is frequently overexpressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…UCA1 promotes the progression of melanoma by sponging miR-28-5p [22]. In Prostate cancer, UCA1 works as an oncogene by targeting miR-204 [28]. The above studies are consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…UCA1 promotes the progression of melanoma by sponging miR-28-5p [22]. In Prostate cancer, UCA1 works as an oncogene by targeting miR-204 [28]. The above studies are consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Knockdown of UCA1 decreased DLL4 expression of renal cancer cells in vivo (g). Data were shown as mean ± standard deviation (SD) of those biological replicates or samples (*P < 0.05, **P < 0.01) [28][29][30], and our study is also a good example on the relation furthermore. LncRNAs function as miRNAs sponges or decoys that titrate the concentration of miR-NAs and therefore prevent miRNAs binding specific mRNAs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In bladder cancer cells, LncRNA UCA1 can enhance cell proliferation, metastasis, and drug resistance. [14][15][16][17] It has been reported that UCA1 contributes to the progression of prostate cancer by regulating proliferation and metastasis through inactivation of KLF4-KRT6/13 signaling pathway, 18 and functioning as a sponge for miR-184, 19 miR-204, 20 or miR-498. 21 Moreover, UCA1 promotes progression of colon cancer 22 and osteosarcoma, 23 and correlates with poor prognosis of ovarian cancer patients.…”
mentioning
confidence: 99%